The influence of built environment characteristics on neighbourhood crime patterns in government subsidised housing developments : the case of Cape Town, South Africa - Ngema, Samukele Manqoba (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2024.